Effectiveness of Disaster Adaptation and Mitigation Comics to Improving Disaster Response Literacy of Senior High School Students Through Problem-Based Learning Model Based on Wonosobo Local Potential - Sumardi, Sumardi; Ngabekti, Sri; Saptono, Sigit (Unnes Science Education Journal, 2024)
This research aims to test implementability, effectiveness, describe the characteristics of the Wonosobo local potential-based disaster adaptation and mitigation comics developed. The devices developed are syllabus, lesson plans, and teaching materials in the form of comics. The research sample for the limited scale trial was 10 X grade students using purposive sampling technique. The research population in a wide-scale trial with a Pretest-postest control group design, class X.1 as an experimental class of 30 students and class X.2 as a control class of 31 students. The results showed that the Wonosobo local potential-based disaster adaptation and mitigation comic was suitable for use. The increase in learning outcomes (N-Gain) in the experimental class of 60% is in the medium category or the N-gain interpreta tion category is quite effective. Based on the achievement of KKM, 97% of students reached the set KKM of 68. The conclusion in this study is that the Wonosobo local potential-based disaster adaptation and mitigation comics developed are de clared very valid, very good implementation, and effective for use in learning activi ties on environmental change material. The characteristics of the Wonosobo local potential-based disaster adaptation and mitigation comics developed present data, photos of disaster events and environmental damage in Wonosobo Regency, so that the Problem Based Learning (PBL) learning model can be carried out optimally. Comics of disaster adaptation and mitigation based on Wonosobo local potential are recommended to be used by Biology Teachers in Wonosobo Regency in learning environmental change material.